A Pilot Study Testing the Efficacy of dCBT in Patients With Cancer Experiencing Sleep Problems - Chung, Kyong-Mee; Suh, Yung Jae; Chin, Siyung; Seo, Daesung; Yu, Eun-Seung; Lee, Hyun Jeong; Kim, Jong-Heun; Kim, Sang Wun; Koh, Su-Jin (Frontiers in Psychology, 2022)
Objective: This pilot study aimed to evaluate the efficacy of a digital cognitive behavioral therapy (dCBT) in patients with cancer experiencing sleep problems. Methods: A total of 57 participants aged 25–65 years (6M: 51F with a mean of 42.80 years and a standard deviation of 14.15 years) were randomly assigned to 3 groups —21 participants to a dCBT program (HARUToday Sleep), 20 participants to an app-based attentional control program (HARUCard Sleep), and 16 participants to a waitlist control group— and evaluated offline before and after the program completion. Of the 57 participants, there were a total of 45 study completers, 15 participants in each group. The dependent variables were sleep quality scores, measured by the Pittsburgh Sleep Quality Index (PSQI) and health-related quality of life scores, measured using the Short-Form 36 (SF-36), and attentional bias scores from a dot-probe computer task. Results: For both the intention-to-treat (N=57) and study-completers analyses (N=45, 15 for each group), a significant increase supported by a large effect size was found in the quality of sleep score of the HARUToday Sleep group compared to both the app-based attentional control and the waitlist control group. However, no significant changes were found in the quality of life and attentional bias scores. Conclusions: Our results suggest that the HARUToday Sleep app has the potential to serve as an intervention module to enhance the sleep quality of patients with cancer experiencing sleep problems.